Green Synthesized Ceo2 Nanostructures On Ceo2 And Eu Doped Ceo2 As Passivation Layer For Silicon Based Metal-Oxide-Semiconductor Devices - Nsar, Saad Milad Ali (2024)
This research presented a green synthesis of cerium oxide (CeO2) nanostructures using P. amaryllifolius leaves extract deposited on CeO2 and Europium (Eu3+) doped CeO2 as passivation layer for silicon-based metal-oxide-semiconductor devices. The effects of adding monoethanolamine (MEA) and CeO2 seed layers for the growth of CeO2 nanostructures were investigated. Findings revealed that CeO2 seed layers played an important role in yielding a lower leakage current density (J) (~ 2.5 x 10-6 A cm-2 at gate voltage (Vg) = 2V) when compared with MEA addition due to the improvement of oxygen-rich condition in the CeO2 samples by the seed layers. The effects of post-deposition annealing temperature (600, 700, 800, 900˚C) and ambient (nitrogen-oxygen-nitrogen, forming gas-oxygen-forming, and argon-oxygen-argon) onto structural, morphological, optical, and electrical characteristics of CeO2 and Eu3+-doped CeO2 seed layers were studied. Optimisation of the findings showed that a better J-Vg characteristic was achieved at 800˚C regardless of ambient while the use of nitrogen-oxygen-nitrogen outperformed other ambient because of the passivation of nitrogen to reduce the formation of low dielectric constant (k) silicon dioxide at the CeO2/Si interface. The growth of CeO2 nanostructures on 1 layer of CeO2 seed layer surpassing other samples having 3, 5, and 7 layers has attained good results in terms of a high k value (16.19), a large direct bandgap (3.98 eV), a low J of 5.07 x 10-11 A cm-2 at Vg = 5V as well as large breakdown voltage (12.82 V).